2016
DOI: 10.1108/medar-07-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Developing soft skills (also known as pervasive skills)

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 44 publications
2
50
0
1
Order By: Relevance
“…The empirical results of this study, namely that simulation is perceived by training officers to be effective in the evaluation of competency in management accounting skill areas, are supported by the literature as both Van der Merwe (2013) and Viviers et al (2016) found simulation to be invaluable to learning.…”
Section: Bishopsupporting
confidence: 64%
See 1 more Smart Citation
“…The empirical results of this study, namely that simulation is perceived by training officers to be effective in the evaluation of competency in management accounting skill areas, are supported by the literature as both Van der Merwe (2013) and Viviers et al (2016) found simulation to be invaluable to learning.…”
Section: Bishopsupporting
confidence: 64%
“…De Villiers (2015) recently concluded that the development of a simulation instrument in specifically audit education is invaluable to learning. A study by Viviers, Fouché and Reitsma (2016), however, revealed that active learning methods are developed on all areas of financial accounting, auditing, managerial accounting and finance, but none on taxation. Consequently, an educational game was developed to evaluate taxationrelated competencies.…”
Section: Bishopmentioning
confidence: 99%
“…Mixed methods are generally characterised by a combination of questionnaires and focus groups or interviews (Stone 2015;Viviers et al 2016). Qualitative methods involve action research (Kirstein & Kunz 2015), case studies (Kirstein & Kunz 2016), focus group discussions (Barac et al 2016), and interviews (Atkins & Maroun 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Stainbank and Gurr (2016) study whether accounting students in South Africa find social networking sites useful for their learning. Viviers, Fouché and Reitsma (2016) evaluate the usefulness of an educational game to develop soft skills. Van Oordt and Mulder (2016) describe the consequences of implementing basic e-learning tools in an undergraduate taxation curriculum.…”
Section: Accounting Education (Ed)mentioning
confidence: 99%
See 1 more Smart Citation